Promoting Security in Africa through Regional Economic Communities (RECs) and the African Union's African Peace and Security Architecture (APSA). Issue 1 (January 2017) - Arthur, Peter
The last two decades have seen African countries adopt a new security approach through the activities of regional economic communities (RECs) and the African Union's (AU) African Peace and Security Architecture (APSA). This article argues that despite progress in conflict prevention and the promotion of peace, defence and security through the APSA and RECs, challenges do remain. In particular, factors such as financial costs involved, the inadequate funds available for peace and security missions, conflicting interests and lack of agreement, poor co- ordination and inadequate human and logistics capacity have constrained the ability of African countries to achieve their peace and security agenda. Thus, for peace and security efforts being undertaken by the AU and RECs to be effective, the actors involved should have not only the requisite capacity but also political will and commitment, and cooperation among members and with the international community should remain crucial to the process.